2011
DOI: 10.1093/infdis/jir166
|View full text |Cite
|
Sign up to set email alerts
|

The Americas: Paving the Road Toward Global Measles Eradication

Abstract: The success of measles elimination strategies in the Americas suggests that global measles eradication is attainable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 8 publications
0
34
0
2
Order By: Relevance
“…1,32,33 In this study, we found a substantial reduction in the number of measles cases over a ten-year period in Tianjin, China, following implementation of two municipality-wide SIAs. There was a dramatic reduction in the incidence of disease in non-locals, whereas incidence stayed more stable in locals.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…1,32,33 In this study, we found a substantial reduction in the number of measles cases over a ten-year period in Tianjin, China, following implementation of two municipality-wide SIAs. There was a dramatic reduction in the incidence of disease in non-locals, whereas incidence stayed more stable in locals.…”
Section: Discussionmentioning
confidence: 54%
“…There was a dramatic reduction in the incidence of disease in non-locals, whereas incidence stayed more stable in locals. SIAs have been shown to be key in eliminating measles in the Americas, 1 and reducing the incidence of disease in Eastern Europe. 32 A study of 15 province-wide SIAs in China during 2004-2008 found that there was on average an 88.1% decrease in measles incidence the year after an SIA compared to the average rate in the preceding five years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of measles vaccines for over 30 y, as well as the implementation of measles control programs, has led to a substantial decline in global measles morbidity and mortality, and many countries have now moved from a control to an elimination phase. 1 Measles elimination is defined as the absence of endemic measles transmission in a defined geographical area for >12 months in the presence of a well-performing surveillance system.…”
Section: Introductionmentioning
confidence: 99%
“…Même si on a réussi à interrompre la transmission du virus de la rougeole endémique dans la Région des Amériques en 2002 (6), la transmission endémique subsiste dans cinq autres régions de l'Organisation mondiale de la Santé (OMS), soit l'Afrique, la Méditerranée orientale, l'Europe, l'Asie du Sud-Est et le Pacifique occidental. Le Canada continue donc de courir le risque d'une importation du virus de la rougeole.…”
Section: Introductionunclassified